A Noether Theorem on Unimprovable Conservation Laws for Vector-Valued Optimization Problems in Control Theory - Torres, Delfim F. M. (Georgian mathematical journal, 2006)
We obtain a version of Noether's invariance theorem for optimal control problems with a finite number of cost functionals. The result is obtained by formulating E. Noether's result for optimal control problems subject to isoperimetric constraints, and then using the unimprovable (Pareto) notion of optimality. It was A. Gugushvili who drew the author's attention to a result of this kind that was posed as an open mathematical question of a great interest in applications of control engineering.